Man vs. machine: can AI outperform ESL student translations? - Alkhofi, Anas (Frontiers in Artificial Intelligence, 2025)
This study compares the quality of English-to-Arabic translations produced by Google Translate (GT) with those generated by student translators. Despite advancements in neural machine translation technology, educators often remain skeptical about the reliability of AI tools like GT and often discourage their use. To investigate this perception, 20 Saudi university students majoring in English and Translation produced human translations in Arabic. These student-generated translations, along with their GT equivalents, were rated by 22 professors with experience in language-related fields. The analysis revealed a significant preference for GT translations over those produced by students, suggesting that GT’s quality may exceed that of student translators. Interestingly, while GT translations were consistently rated higher, instructors often misattributed the better translations to students and the poorer ones to GT. This reveals a strong perceptual bias against AI-generated translations. The findings support the inclusion of AI-assisted translation tools in translation training. Incorporating these tools will help students prepare for a job market where AI is playing an increasingly important role. At the same time, educators should adopt strategies incorporating AI tools without sacrificing the development of students’ core translation skills.